Efficient Synthesis of 2‐Substituted Phthalimides from Phthalic Acids in One Step. Issue 33 (25th September 2013) - Chorell, Erik; Chorell, Elin
Abstract: Efficient procedures for synthesizing 2‐substituted phthalimide (isoindole‐1, 3‐dione) analogues starting from phthalic acids have been developed by using experimental design. The phthalimide central fragment frequently appears in biologically active compounds, materials, catalysts, and fluorescent probes, and therefore the development of general, fast, and convenient synthetic methods to this scaffold under neutral, acidic, and basic conditions would be attractive. After an initial screening, the use of acetonitrile, acetic acid, or pyridine in combination with microwave heating proved most promising. Experimental design was applied to these conditions to optimize the time, temperature, and concentration. This strategy has successfully generated synthetic methods that have been used to synthesize a series of phthalimides from phthalic acids and various amines or anilines in excellent yields. The developed methods have proven to be general, fast, convenient, and economic, and thus are expected to have broad utility to efficiently construct novel compounds for future biological and chemical applications. Abstract : Efficient procedures for synthesizing 2‐substituted phthalimide (isoindole‐1, 3‐dione) analogues starting from phthalic acids have been developed by using experimental design. The developed methods are fast, general, high‐yielding, do not use additives, and are based on 1:1 molar ratios.